A Study on Determinants of Customer Satisfaction in E-enabled bus booking platforms - Deogadkar, Amol (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
E-enabled ventures (especially the online bus booking services) have witnessed impressive growth in India during last decade. Especially after COVID-19, customer shift towards online services is expected to augment. This paper is an attempt to develop a scale for determinants of customer satisfaction amongst the existing users of online bus booking (e-enabled platform).Using e-SERVQUAL model by Parasuraman et al. (2005), a draft instrument was designed. Since online bus services also includes physical experience of services offered, Tangibility factor was added in the construct. The questionnaire was tested on a sample of existing users of online bus booking services (n=105). After checking for the adequate reliability score, Exploratory factor Analysis (EFA) was performed. It resulted into extraction of four factors such as Contact, Fulfilment, Privacy and Responsiveness, accounting for 50.5% of total variance explained. Validating this scale on a larger sample for generalisation of the results would be the future agenda of research. Development of India specific scale for e-enabled business models in public transports can be considered as one of the major contribution of this study.